Asian corporate recovery : findings from firm-level surveys in five countries - Dwor-Frecaut, Dominique; Colaço, Francis X.; Hallward-Driemeier, Mary; World Bank. (Washington, D.C. : World Bank, 2000)
The article presents the main findings of surveys of 3,700 manufacturing firms in Indonesia, The republic of Korea, Malaysia, the Philippines, and Thailand, conducted by the governments of these countries from November 1998 to February 1999
Conference papers.
gp. 23/01/2019
Loan
Keywords: Financial crises; Industrial management; Southeast Asia